The Infant of Brussels: The Manneken-Pis as Christ Child. (1st December 2003) - Emerson, Catherine
The Manneken-Pis is the well-known bronze statue of a small boy in a Brussels fountain. Although generally seen as a cultural icon, it seems that many parallels may be drawn between the Manneken-Pis and images of the Christ Child, and indeed the little statue has attracted a number of cultural practices more normally associated with religious icons.